ANALISIS EFISIENSI PEMASARAN KUBIS DI KECAMATAN GISTING KABUPATEN TANGGAMUS - Muhammad Fajar Ali; Suriaty Situmorang; Ktut Murniati (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
This research aims to analyze the efficiency of cabbage marketing system in Gisting Subdistrict.  The research was conducted purposively in Gisting Atas Village and Gisting Permai Village in April-September 2016.  Farmer respondents were chosen randomly and marketing channel respondents were taken by tracing marketing networks. Data analysis included analysis of marketing system efficiency.  Data analysis method using S-C-P method. The results showed that the marketing system of cabbage in Gisting Subdistrict were inefficient with producer share (Ps) above 54,49  percent, with the following conditions: (a) the market structure was an imperfect competition. (b) the market conduct: cabbage farmers had no difficulty in marketing their product. (c) the market performance: there were twelve marketing channel; marketing margin and Profit Margin Ratio were relatively high, and the elasticity of price transmission was more than one.  Key words: cabbage, efficiency, marketing, S-C-P model